LC-HRMS-Based Metabolomics Approach Reveals Antioxidant Compounds from Centella asiatica Leaves Extracts - Riva Silvia; Wulan Tri Wahyuni; Eti Rohaeti; Siti Aisyah; Dewi Anggraini Septaningsih; Alfi Hudatul Karomah; Mohamad Rafi (Indonesian Journal of Chemistry)
Centella asiatica is a medicinal plant widely used as a traditional medicine due to several biological activities, such as antioxidants in Indonesia. This study aims to identify the active antioxidant compounds of C. asiatica leaves extract using a liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS)-based metabolomics approach. Extracts were prepared using different concentrations of ethanol p.a., i.e. 70% ethanol, 50% ethanol, 30% ethanol, and water. Antioxidant activity was tested using the 2,2-diphenyl-1-picrylhydrazyl method. The results showed the highest antioxidant activity was C. asiatica extracted by 70% ethanol with IC50 of 72.48 ± 2.42 µg/mL. The positive control was ascorbic acid, having an IC50 value of 3.38 ± 0.04 µg/mL. Ascorbic acid and 70% ethanol extract have strong antioxidant activity. Metabolite profiling using LC-MS/MS could identify 35 metabolites consisting of flavonoids, fatty acids, phenolics, terpenes, and several other groups of compounds. Orthogonal partial least squares-discriminant analysis classified the metabolites into active (ethanol 70% and ethanol 50%) and inactive (ethanol p.a., ethanol 30%, and water) antioxidants. Five metabolites have potential as antioxidants, namely 4,5-dicaffeoylquinic acid (11), kaempferol (13), and three unknown compounds.